Meningkatkan Keterampilan Pemecahan Masalah, Berpikir Kritis, dan Memberikan Pendapat, Menggunakan Model Pena pada Muatan Pendidikan Pancasila Kelas V SDN Kuin Utara - Siti Noor Halisa; Ari Hidayat (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The low mastery of problem solving, critical thinking, and opinion-expressing skills among Grade V students at SDN Kuin Utara 1 was evident from baseline data showing that 65% of students tended to be passive, 75% struggled to turn a problem into a question, 70% found it difficult to draw logical conclusions, and 82% were not yet confident in expressing their opinions. This study aimed to describe teacher and student activities and to analyze the improvement of these three skills through the implementation of the PENA model in Pancasila Education. The novelty of this study lies in the integration of Problem-Based Learning (PBL), Example Non-Example (ENE), and Numbered Head Together (NHT) into a single learning model, PENA, designed to develop these three 21st-century skills simultaneously. This study used a Classroom Action Research (CAR) design carried out in four meetings, involving 22 fifth grade students of the 2025/2026 academic year at SDN Kuin Utara 1 Banjarmasin. Qualitative data were obtained through observation of teacher activity, student activity, and the three target skills, while quantitative data were obtained from individual cognitive learning tests. The results showed consistent improvement at every meeting: teacher activity increased from a score of 27 to 32 (very good criterion), and classical student activity increased from 18% to 91% (very active criterion). Students' problem-solving, critical thinking, and opinion-expressing skills increased from 23%, 18%, and 18% respectively to 91% (very skilled criterion) by the fourth meeting, while classical mastery of cognitive, affective, and psychomotor learning outcomes rose from 59% to 100%, exceeding the minimum success indicator of ≥76%. It can therefore be concluded that the implementation of the PENA model is effective in improving learning activity as well as problem-solving skills, critical thinking, and the ability to express opinions among fifth-grade students in Pancasila Education.